Multiple embryonic origins of nitric oxide synthase-expressing GABAergic neurons of the neocortex - Magno, Lorenza; Oliveira, Marcio G.; Mucha, Mariusz; Rubin, Anna N.; Kessaris, Nicoletta (Frontiers in Neural Circuits, 2012)
Cortical GABAergic interneurons in rodents originate in three subcortical regions: the medial ganglionic eminence (MGE), the lateral/caudal ganglionic eminence (LGE/CGE) and the preoptic area (POA). Each of these neuroepithelial precursor domains contributes different interneuron subtypes to the cortex. nNOS-expressing neurons represent a heterogenous population of cortical interneurons. We examined the development of these cells in the mouse embryonic cortex and their abundance and distribution in adult animals. Using genetic lineage tracing in transgenic mice we find that nNOS type I cells originate only in the MGE whereas type II cells have a triple origin in the MGE, LGE/CGE and POA. The two populations are born at different times during development, occupy different layers in the adult cortex and have distinct neurochemical profiles. nNOS neurons are more numerous in the adult cortex than previously reported and constitute a significant proportion of the cortical interneuron population. Our data suggest that the heterogeneity of nNOS neurons in the cortex can be attributed to their multiple embryonic origins which likely impose distinct genetic specification programs.